2022
DOI: 10.1111/pbi.13950
|View full text |Cite
|
Sign up to set email alerts
|

Linking plant functional genes to rhizosphere microbes: a review

Abstract: Summary The importance of rhizomicrobiome in plant development, nutrition acquisition and stress tolerance is unquestionable. Relevant plant genes corresponding to the above functions also regulate rhizomicrobiome construction. Deciphering the molecular regulatory network of plant‐microbe interactions could substantially contribute to improving crop yield and quality. Here, the plant gene‐related nutrient uptake, biotic and abiotic stress resistance, which may influence the composition and function of microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 279 publications
0
11
0
Order By: Relevance
“…Transcriptomics analysis revealed that beneficial and anti-pathogenic microbes correlated positively with the root MEblue module, whereas potential pathogens correlated negatively with the root MEblue module. The results of several studies have shown similar findings with root-associated microbes [64,65]. Plant functions can be reg-ulated directly or indirectly by microbes [66,67].…”
Section: Discussionmentioning
confidence: 58%
“…Transcriptomics analysis revealed that beneficial and anti-pathogenic microbes correlated positively with the root MEblue module, whereas potential pathogens correlated negatively with the root MEblue module. The results of several studies have shown similar findings with root-associated microbes [64,65]. Plant functions can be reg-ulated directly or indirectly by microbes [66,67].…”
Section: Discussionmentioning
confidence: 58%
“…Finally, recent research has led to the discovery that plant functional genes, and in particular symbiotic signaling genes in legumes, are involved in modulating the structure of the root-associated microbiota and the interactions among these communities ( Zgadzaj et al., 2016 ; Thiergart et al., 2019 ; Liu et al., 2023 ). Legumes can establish mutualistic interactions with rhizobia and arbuscular mycorrizal fungi (AMF) that induce symbiotic signaling pathways involving specific components but also sharing some common components ( Oldroyd, 2013 ).…”
Section: The Rhizosphere Microbiome: a Hotspot For Microbial Interact...mentioning
confidence: 99%
“…Some of the N-responsive genes help in the regulation of rhizomicrobiome and this molecular regulatory network of plant-microbe interactions could improve crop production [70]. Microbiomes have a great role in structuring plant phenotype by induction of more lateral roots for efficient absorption of nutrients and thus help in increasing NUE in crops [71].…”
Section: Role Of Microbes In Nitrogen Uptake and Trnsportmentioning
confidence: 99%